Quantitative measurement of displacement in photopolymer layers during holographic recording using phase shifting electronic speckle pattern interferometry - Moothanchery, Mohesh (2016)
The aim of this study is to determine the displacement profile due to shrinkage in acrylamide-based photopolymer layer during holographic recording. Using phase shifting electronic speckle pattern interferometry the displacement at each pixel in the image of the object is measured by phase shifting technique so that a complete displacement profile of the object can be obtained. It was observed that the displacement profile is Gaussian and resembles to the profile of the recording beam. We observed an increase in shrinkage from 2 μm at 20 seconds of recording to 7.5 μm after 120 seconds of recording. The technique allows for real time measurement of the shrinkage profile.